Challenges of Artificial Intelligence in Enhancing E-Governance - Touq, Mona (Journal of Legal and Political Studies, 2025)
Artificial intelligence is a model for overcoming traditional administrative stagnation, which is often constrained by routine transactions in Arab government institutions. Instead, it promotes the adoption of electronic systems based on innovation in applications and data technology. This raises the following research question: To what extent does artificial intelligence contribute to enhancing responsible and secure electronic governance in government institutions? This research is significant because it highlights how artificial intelligence technologies can benefit citizens and the nation. This necessitates that government institutions adopt a strategic approach that includes developing employees' technological skills through specialized training, creating an interactive and supportive work environment that fosters change, and implementing legislative reforms. The study examines how AI tools enhance performance, improve efficiency, execute tasks, and analyze big data. The analytical approach attempts to explore potential challenges such as combating administrative corruption, enhancing cybersecurity, protecting governmental and personal data, reducing errors, and addressing threats or breaches to answer the proposed research question and provide conclusions that highlight key characteristics. Additionally, an operational approach was used to classify and analyze information, drawing clear conclusions regarding monitoring the legitimacy of decisions and assessing risks associated with the practical application of artificial intelligence. The research presents significant findings that contribute to resolving administrative challenges. It emphasizes that AI-driven electronic governance enhances government services, alleviates burdens on citizens, increases institutional productivity, and achieves strategic objectives for sustainable economic growth, ensuring quality and transparency in the state's vital sectors. Keywords: Artificial Intelligence, Electronic Governance, Cybersecurity, Cloud Computing.
Keywords: Artificial Intelligence; Electronic Governance; Cybersecurity; Cloud Computing